Utilizing Dynamic Programming for Optional Shortest Route Determination - Winda, Winda Ade Fitriya B; Andre Anusta Barus (International Journal of Health Engineering and Technology, 2023)
Fuel prices have seen a significant increase. This encourages individuals to save costs on their fuel expenditure by finding the shortest route to their destination. The shorter the route, the less fuel will be released. This study answers the challenge of determining the shortest route between BTN Lembah Furia Sentani in Jayapura Regency to the Department of Mathematics of Cenderawasih University in Papua Province. Many roads can be passed from BTN Lembah Furia Sentani in Jayapura Regency, to the Department of Mathematics of Cenderawasih University in Papua Province. As is well known, that the streets in Jayapura City have many alternative roads with different characters. The existing road characteristics include density, physical condition of the road and the size of the road width. With the existing road character, it can be assumed that each road has an average travel length. This average value is used as the cost of the road.  To solve this problem, a dynamic programming approach is used to identify optimal routes while minimizing costs. The dynamic program utilizes analyzed and calculated data to yield the best outcomes. The results indicate that the quickest path from BTN Lembah Furia Sentani to the Mathematics Department at Cenderawasih University is via Komba Netar Bridge, GKI Petrus Waena Church, covering a distance of 25.2 kilometers